Perbandingan Model Pembelajaran Problem Based Learning dengan Guided Discovery Learning terhadap Keaktifan Siswa Kelas X SMA Negeri 1 Ngawi Tahun Pelajaran 2013.2014 - Pranoto, Pranoto; Harlita, Harlita; Santosa, Slamet (Bioedukasi: Jurnal Pendidikan Biologi, 2017)
ABSTRACT- The purpose of this research is to know the comparison of problem based learning models with Guided discovery learning to activities of students of X grade students at SMA Negeri 1 Ngawi in academic year 2013/2014. This study was a quasi experimental research. The research design was used post-test only nonequivalent control group design. This research applied problem based learning models and Guided Discovery Learning at experimental group. The population of this research was all of X grade students at SMA Negeri 1 Ngawi in academic year 2013/2014. Sampling techniques used cluster sampling that choosed X MIPA 4 experiment group I and X MIPA 6 as Experiment group II. Techniques of collecting data were test and non-test methods. The test method examination test. The non-test method included observation of activities student and documentation.  The hypotheses analyzed by t-test. This research concluded that there are differences activities of student to application of problem based learning and Guided Discovery Learning of grade students at SMA Negeri 1 Ngawi in academic year 2013/2014.Keywords : activities., problem based learning., Guided discovery learning.